Early Triassic ichthyopterygian fossils from the Russian Far East - Nakajima, Yasuhisa; Shigeta, Yasunari; Houssaye, Alexandra; Zakharov, Yuri D.; Popov, Alexander M.; Sander, P. Martin (Scientific reports, 2022)
Ichthyopterygia is a major clade of reptiles that colonized the ocean after the end-Permian mass extinction, with the oldest fossil records found in early Spathian substage (late Olenekian, late Early Triassic) strata in the western USA. Here, we describe reptilian remains found in situ in the early Spathian Neocolumbites insignis ammonoid zone of South Primorye in the Russian Far East. Specimen NSM PV 23854 comprises fragmentary axial elements exhibiting a combination of morphological characteristics typical of Ichthyopterygia. The cylindrical centra suggest that the specimen represents a basal ichthyopterygian, and its size is comparable to that of Utatsusaurus . Specimen NSM PV 24995 is represented by a single limb bone, which is tentatively identified as an ichthyopterygian humerus. With a body length of approximately 5 m estimated from the humeral length, NSM PV 24995 represents one of the largest specimens of early Spathian marine reptiles known to date. Such size variation among the earliest ichthyopterygians might suggest an explosive diversification in size immediately after the end-Permian mass extinction. Both vertebrae and humerus specimens exhibit an extremely cancellous inner structure, suggesting a high degree of aquatic adaptation in ichthyopterygians, despite their short history of evolution in the ocean.